Piaget’s And Vygotsky’s Constructivist Theories - GHAOUR, NESRINE (University of El-oued, 2018)
Le constructivisme est le courant qui permet aux apprenants de construire leurs propres savoirs. On distingue deux grandes écoles: le constructivisme individuel de Piaget et le constructivisme social de Vygotsky. Pour Piaget, assimilation, accommodation entre autres sont essentiels pour un apprentissage individuel. Tandis que pour Vygotsky, puisque c’est social, la culture et l’interaction avec la société conditionne l’apprentissage d’un individu Constructivism is based on the premise that learners construct their own learning from their experiences. Constructivism is of two waves: Piaget’s psychological/individual constructivism; ‘the first wave constructivism’ or ‘solo constructivism’, and Vygotsky’s social constructivism; ‘the second wave constructivism’. The first, Piaget constructivism, is concerned with knowledge that focuses on the individual and psychological sources of learning. For Piaget, assimilation, accumulation and equilibratium are essential processes for effective learning. The latter, Vygotsky’s Social constructivist theory views language learning as socialization, not only as cognition. It recognizes that social interaction and culture are important in shaping individuals’ learning. here “Zone of Proximal Development” (ZPD), mediation, and scaffolding are the basic terms.
Article .Ex Professor. Vol 03. N 01 Université d'El-Oued
Keywords: constructivism, Piaget’s constructivism, assimilation, accommodation, equilibrium, Vygotsky’s constructivism, ZPD, scaffolding, mediation; constructivisme, constructivisme de Piaget, assimilation, accommodement, équilibre, constructivisme de Vygotsky, ZPD, échafaudage, médiation